If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + 9(y + -6) = 0 Reorder the terms: 36 + 9(-6 + y) = 0 36 + (-6 * 9 + y * 9) = 0 36 + (-54 + 9y) = 0 Combine like terms: 36 + -54 = -18 -18 + 9y = 0 Solving -18 + 9y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 9y = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 9y = 0 + 18 9y = 0 + 18 Combine like terms: 0 + 18 = 18 9y = 18 Divide each side by '9'. y = 2 Simplifying y = 2
| 4sin^2x/(4-4sin^2x)^0.5 | | 3000=L*(L-8) | | e^2lnx=0 | | 1/4*(x-1)=(x-4)/6 | | 8*9/8x-8*36 | | 6y=x^2 | | x+x+1+x-13=118 | | y=80+6(21) | | 3/U-8/V | | 3/U-8?V | | (15-6x)/3=5 | | (x(0.050))/(0.200-x) | | 2k/3=6 | | 14x+6=16x+4 | | x(0.05)/.2-x | | 50x^3-8x=0 | | 4x+13=2x-4 | | 5/6=n/8 | | 3(5x+2)=8x+34 | | 300/16= | | -2/7(y-114)-1/21y= | | -2/7y-14) | | 3/16x1/100 | | -2/7y-1/21y= | | 14-1/21y= | | 3/16x100= | | 8=8h+18 | | -2/7(y-14) | | 5-1/3x=2 | | -p-38=-6(-6p+6)-2 | | -6/5(y-10)-1/15y= | | (6x+5)(x-4)=6 |